Australian Asylum Seeker Policy from Three Perspectives - Zoe Bell (Refuge)
Antje Missbach. The Criminalisation of People Smuggling in Indonesia and Australia. Routledge, 2022, 224 pp. ISBN: 9781032078496 (paperback).